LEGAL IMPLICATIONS OF WITHDRAWAL OF CRIMINAL CASE COMPLAINTS AT THE INVESTIGATION LEVEL - Syahputra, Maulana Juardi; Hafidz, Jawade (UNISSULA Semarang, 2024)
This study aims to determine the legal implications of withdrawing criminal case reports/complaints at the investigation level and to determine and analyze the obstacles to withdrawing criminal case reports/complaints at the investigation level and their solutions. This study uses a Sociological Legal approach and analytical descriptive research type. Based on the research, it is concluded that the person who has the right to withdraw a complaint according to the 1946 Criminal Code and the 2023 Criminal Code is the person who files the complaint within 3 (three) months from the date it was filed and the complaint can be withdrawn by the complainant. Several articles in the 1946 Criminal Code and the 2023 Criminal Code as well as PERPOL Number 8 of 2021 regulate criminal acts for which complaints can be withdrawn at the investigation level.